HUBUNGAN FAKTOR-FAKTOR INTERNAL PERAWAT DENGAN PENGETAHUAN PERAWAT TENTANG PENERAPAN STRATEGI PELAKSANAAN PADA PASIEN DENGAN GANGGUAN HALUSINASI - Arisandy, Widya (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Knowledge is the result of ?know? and this is happening after they made a sensing towards an object certain .Sensing towards an object occur through panca human senses the sight , hearing , of smell , taste and touched with own .Knowledge about the implementation of the nurse strategy is obliged to understandable and in understand by a nurse soul .Many things can affect knowledge a nurse soul both internally and externally.Strategy the implementation of the act of nursing is a in made as a guide by a nurse if when interacting with disorder patients hallucinations.The purpose of research to know relations factors internal a nurse with knowledge nurse in the application of the implementation of the strategy in patients with disorder hallucinations in inpatient Rooms Hospital Ernaldi Bahar The Province Of South Sumatera 2017 . The kind of research done is research quantitative by using the method survey analytic approach in cross sectional .Technique the sample collection that is using a technique the sample collection total of sampling , the number of the sample are always 33 people .To research this independent variable consists of education , length of employment and the days of while dependent variable is knowledge nurse about strategy the implementation of the hallucinations . the results of this research was obtained one variable are associated than 3 variable internal factors researched namely working time with the results of p-value 0,011. Researchers hope from the results of this research , nurses can identify any factor that could affect the knowledge nurses and also can be used to understand the science of psychiatric Keywords       : Nurses Knowledge, Strategy Implementation Hallucinations